Analisis Pengaruh Pertumbuhan Ekonomi Terhadap Realisasi Investasi Asing Dan Investasi Dalam Negeri Di Indonesia Tahun 2018-2021 - Putri Amanda; Tazkia Ayu Alharani.YS; Putri Indriyanti; Retno Sri Rindiyani (Pusat Riset dan Inovasi Nasional, 2022)
Penanaman Modal Asing (PMA) and Penanaman Modal Dalam Negeri (PMDN) are important sources of financing for developing regions and can make a significant contribution to development. As a component of capital flows, Foreign Direct Investment (FDI) is considered a relatively stable inflow compared to other capital flows, such as portfolio investment and foreign debt. A country's economy relies on investment to solve various problems, crises, and economic challenges. This is because investing in certain sectors of the economy can quickly change the various economic challenges facing a country. Both private and public investment bring many benefits, including job creation. The purpose of this study is to analyze the impact of domestic and foreign investment on economic growth. This type of research is quantitative research. The research instrument used is documentation of research instruments through books and scientific journals. Data analysis using multiple regression method. As a result, it can be seen that foreign investment has a large positive effect on economic growth. Foreign direct investment helps Indonesia achieve stable national development. But domestic investment has no effect on economic growth. The implementation of this research is the need for the government's role as a regulator to support increased domestic and international investment in order to encourage Indonesia's economic growth.